Enhancing the Phenolic Content of Bio-Oil by Acid Pre-Treatment of Biomass - Nurgül Özbay; Elif Yaman (International Journal of Renewable Energy Development, 2018)
Pyrolysis of lignocellulosic biomass with acidic pre-treatment to produce valuable bio-chemicals has been carried out in an integrated pyrolysis-gas chromatograph/mass spectrometry system. Three different waste biomasses (fir wood sawdust, pine wood sawdust and nutshell) were subjected to acidic solution to specify the acid pre-treatment effect on biomass chemical structure, thermal degradation profile and pyrolysis products. Post acid pre-treatments, the changes in the biomasses and thermal degradation profile were studied through proximate, structure and ultimate analysis and thermogravimetric. The pre-treatment significantly reduced the inorganic, cellulose and hemicellulose content in biomass samples. According to the pyrolysis experiment results, acid pre-treatment provided the increasing of the amount of phenolic in the degradation products at 10 min pyrolysis time. All the results would assist further understanding of thermal decomposition and thermo-chemical application for bio-fuels and bio-chemicals of fir wood sawdust, pine wood sawdust and nutshell.Article History: Received January 15th 2018; Received in revised form May 24th 2018; Accepted 7th June 2018; Available onlineHow to Cite This Article: Ozbay, N. and Yaman, E (2018) Enhancing the Phenolic Content of Bio-Oil by Acid Pre-Treatment of Biomass. Int. Journal of Renewable Energy Development, 7(2), 163-169.https://doi.org/10.14710/ijred.7.2.163-169